Relationship between Body Mass Index and Tooth Decay in a Population of 3–6-Year-Old Children in Iran - Leila Shafie Bafti; Maryam Alsadat Hashemipour; Hamidreza Poureslami; Zeinab Hoseinian (International Journal of Dentistry)
The aim of the present study was to evaluate the relationship between BMI and tooth decay in a population of Iranian children. In this cross-sectional descriptive/analytical study, 1482 children were selected from kindergartens and preschool centers in Kerman, Iran. The children underwent examination of deciduous teeth (using the dmft index) after determination of height and weight for calculation of BMI. The relationship between BMI (after adjustment for age) and dmft was determined using Poisson’s regression model. The mean of dmft in children with normal BMI was 1.5-fold that in subjects with extra body weight. Age had a significant effect on dmft. In addition, dmft was higher in boys compared to girls. The results of the present study showed that caries rate in the deciduous teeth of 3–6-year-old children decreases with an increase in body weight.